PENGARUH PENGGUNAAN APLIKASI STELLARIUM TERHADAP LITERASI SAINS SISWA PADA MATA PELAJARAN GEOGRAFI DI SMA NEGERI 2 SIRENJA - Abdul Fajar; Exsa Putra; Amalia Novarita; Widyastuti Widyastuti (Universitas Pendidikan Ganesha, 2026)
This study aims to measure the effect of using the Stellarium application on improving the science literacy of Grade X students on solar system material at Sirenja 2 State Senior High School. The method used is a quasi-experiment with a nonequivalent control group design. The research sample consisted of two classes selected purposively, the experimental class (X-A) and the control class (X-C). Data collection included observation of student learning activities, pre-tests and post-tests, as well as questionnaires on student responses to the use of learning media. Data analysis was carried out through several stages of testing, namely reliability testing, normality testing to test data distribution, homogeneity testing to see the similarity of variance between groups, and hypothesis testing using the T-test. The results showed that the average score of the experimental class was 82.00, while the control class had an average score of 63.21. The t-test on the post-test results showed a significance value (Sig. 2-tailed) of 0.000 < 0.05, which means that H₀ was rejected and H₁ was accepted. This indicates that the use of the Stellarium application had a positive effect on improving students' science literacy. In addition, the questionnaire results showed that 30% of students answered (strongly agree) and 64% of students answered (agree), with the remaining 6% answering otherwise. Thus, the experimental class responded positively to learning using Stellarium, stating that the media was interesting, helped their understanding, and increased their curiosity about.